أثر أبعاد التسويق الداخلي على إدارة المعرفة - قحموش, إيمان (Recherches économiques et managériales; No 22 (2017): RECHERCHES ÉCONOMIQUES ET MANAGÉRIALES(Décembre), 2018)
يهدف هذا البحث إلى إبراز أثر أبعاد التسويق الداخلي على إدارة المعرفة، فتنفيذ التسويق الداخلي في المؤسسة يزودها بالكفاءات والقدرات التي ستؤدي إلى تحسين الأداء التنظيمي، ذلك أن التسويق الداخلي ليس فقط التركيز على الموظفين، وإنما هو نشاط ضروري في تنفيذ إدارة المعرفة، وبالتالي اعتباره أداة للتعلم . لذلك يمكن القول، بأن التنفيذ الناجح للتسويق الداخلي يمكن أن يمهد الطريق لتنفيذ ناجح للعمليات التنظيمية مثل نظام إدارة المعرفة . وخلصت هذه الدراسة إلى أن إدارة المعرفة مهمة أساسية للمؤسسات التي تسعى إلى الاستفادة من مواردها البشرية، لذلك فإن ( التحفيز والاتصال الداخلي والتوجه نحو العملاء ) أنشطة تصنع القيمة من خلال تأثيرها على دفع المعرفة من المستويات الضمنية الفردية إلى مستويات صريحة جماعية لضمان استمرارية المؤسسة . الكلمات المفتاحية : إدارة المعرفة، التسويق الداخلي، التحفيز، الاتصال الداخلي، التوجه نحو العملاء . Abstract : This research aims to highlight the impact of internal marketing dimensions on knowledge management. Implementing internal marketing in the enterprise provides it with competencies and capabilities that leads to improve the organizational performance. Internal marketing does not focus only on employees but it is primordial to apply knowledge management. It is considered a tool of learning. Thus, a successful implementation of internal marketing can pave the way for the successful implementation of organizational processes such as the knowledge management system. The study concludes that knowledge management is acrucial task for enterprises seeking to benefit from their human resources, for that reason: Motivation, internal communication and customer orientation are activities that create value through their influence on driving knowledge from implicit individual levels to explicit collective levels which ensures enterprise persistence. Keywords : Knowledge Management, Internal Marketing, Motivation, internal communication, Customer Orientation.